Sustained long-term improvement with clozapine in schizophrenia Clozapina na esquizofrenia grave: melhora duradoura e sustentada - RICARDO DE OLIVEIRA-SOUZA; ROGÉRIO PAYSANO MARROCOS; WAGNER MARTIGNONI DE FIGUEIREDO (Arquivos de Neuro-Psiquiatria)
The present paper reports the long-term use of clozapine in a prospective sample of 46 chronic schizophrenics. In six months, 21 subjects had been excluded for a number of reasons. In four of them the reasons for exclusion were related to lack of response or adverse effects. The median daily clozapine dose was 400 mg in the remaining 25 patients. As a whole, there were remarkable improvements in core dimensions of psychopathology, global cognitive status, and level of functioning. We confirmed that clozapine is effective in a subgroup of schizophrenics with the severest forms of the disease. If tolerated after the first few months it leads to progressive gains in several domains of behavior. Clozapine should be tried in every patient with schizophrenia in whom positive symptoms, disorganization, or bizarre behavior are a matter of incapacitation despite efforts to keep them under control with other drugs. O presente estudo, prospectivo, relata o uso de longo-prazo da clozapina em 46 esquizofrênicos graves, com mais de cinco anos de doença. Com seis meses de uso da droga, 21 indivíduos haviam sido excluídos por diversas razões. Em quatro, a exclusão se deveu a efeitos adversos ou ausência de resposta. A dose mediana de clozapina foi de 400 mg nos demais 25 pacientes. No todo, observamos melhora em dimensões de psicopatologia, estado cognitivo global, e nível funcional. Concluímos que a clozapina é eficaz em um subgrupo de esquizofrênicos com formas graves da doença. Se tolerada depois dos primeiros meses, produz benefícios progressivos em diversos domínios do comportamento. Clozapina deve ser tentada em todo paciente com esquizofrenia incapacitado por sintomas positivos, desorganização, e/ou comportamentos bizarros, que persistem a despeito de esforços para mantê-los sob controle com outras drogas.